2019
DOI: 10.3390/nu11051073
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gut Microbiota Composition on Onset and Progression of Chronic Non-Communicable Diseases

Abstract: In recent years, mounting scientific evidence has emerged regarding the evaluation of the putative correlation between the gut microbiota composition and the presence of chronic non-communicable diseases (NCDs), such as diabetes mellitus, chronic kidney disease, and arterial hypertension. The aim of this narrative review is to examine the current literature with respect to the relationship between intestinal dysbiosis and the insurgence/progression of chronic NCDs, analyzing the physiopathological mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 203 publications
(217 reference statements)
0
98
0
4
Order By: Relevance
“…Recently, much attention has been given to the gut microbiota, considered as a metabolic "organ" which impacts host nutrition, and may influence the bioavailability and bioaccessibility of olive phenolic compounds via biotransformation into other active substances, which have interesting beneficial health properties in bowel diseases [166,183]. Mosele et al [184], in an in vitro model experiment, observed that Ole was rapidly deglycosylated during 6 h of incubation with human fecal microbiota, becoming OleA; the latter was degradated into elenolic acid and HT by microbial esterase activity, until it disappeared after 48 h. On the contrary, HT constantly increased during the same fermentation period.…”
Section: Bioavailability Of Oleuropeinmentioning
confidence: 99%
“…Recently, much attention has been given to the gut microbiota, considered as a metabolic "organ" which impacts host nutrition, and may influence the bioavailability and bioaccessibility of olive phenolic compounds via biotransformation into other active substances, which have interesting beneficial health properties in bowel diseases [166,183]. Mosele et al [184], in an in vitro model experiment, observed that Ole was rapidly deglycosylated during 6 h of incubation with human fecal microbiota, becoming OleA; the latter was degradated into elenolic acid and HT by microbial esterase activity, until it disappeared after 48 h. On the contrary, HT constantly increased during the same fermentation period.…”
Section: Bioavailability Of Oleuropeinmentioning
confidence: 99%
“…One of the key elements driving NCDs intergenerational nature and playing a pivotal role in "the first 1000 days", is the gut microbiome, a highly dynamic organ which is sensitive to environmental factors and that modifies its composition over the host's lifespan [6].…”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that Ni has a toxicological impact on the intestinal ecosystem and, possibly, functions. The qualitative and quantitative dysregulation of the intestinal microbiota setup is indicative of a pathologic condition called dysbiosis, which may cause symptoms of varying types and severity in immunological, metabolic, psychiatric, and intestinal diseases [18,19]. Gut dysbiosis is associated with altered microbial metabolism with a higher production and reabsorption of intestinal bacterial metabolites derived from the breakdown of tryptophan, such as indican (3-indoxyl sulfate) and 3-methyl-indole (also named skatole) [20,21].…”
Section: Introductionmentioning
confidence: 99%